Topical Examples of the Formation of Professional Competence in Future Educators - Bakhtiyor, Suvankulov (European Journal of Life Safety and Stability (2660-9630), 2022)
This article reveals the essence of the concept of competence. The ways of pedagogical development of professional competence in educators are indicated. A complex of competencies is highlighted, which determines the level of development of pedagogical competence, which can be acquired for future teachers.